2023
DOI: 10.1186/s13578-023-01035-1
|View full text |Cite
|
Sign up to set email alerts
|

Bile acid-mediated signaling in cholestatic liver diseases

Abstract: Chronic cholestatic liver diseases, such as primary biliary cholangitis (PBC) and primary sclerosing cholangitis (PSC), are associated with bile stasis and gradually progress to fibrosis, cirrhosis, and liver failure, which requires liver transplantation. Although ursodeoxycholic acid is effective in slowing the disease progression of PBC, it has limited efficacy in PSC patients. It is challenging to develop effective therapeutic agents due to the limited understanding of disease pathogenesis. During the last … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 162 publications
(200 reference statements)
0
7
0
Order By: Relevance
“…For example, primary C24 beta‐muricholic (b‐MCA) bile acid was increased from ~10,000 to 30,000 fmol/g of liver tissue, and from 600 to 3,500 nM in MAPL −/− serum (Fig 2C, Table EV2). In contrast, both precursors and conjugated bile acids were decreased by more than 50% in feces (Fig 2C, Table EV2), suggestive of bile flow stalling through the liver/gallbladder biliary system (cholestasis, typically resulting in tissue damage) or increased reabsorption from the gut into circulation (Zeng et al , 2023). Histological examination of liver and damage markers showed no evidence of cholestasis, as morphology of bile canaliculi was normal, no signs of necrosis were present and serum alanine transaminase/aspartate aminotransferase (ALT/AST) were not changed (Figs 2C–E and EV2B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, primary C24 beta‐muricholic (b‐MCA) bile acid was increased from ~10,000 to 30,000 fmol/g of liver tissue, and from 600 to 3,500 nM in MAPL −/− serum (Fig 2C, Table EV2). In contrast, both precursors and conjugated bile acids were decreased by more than 50% in feces (Fig 2C, Table EV2), suggestive of bile flow stalling through the liver/gallbladder biliary system (cholestasis, typically resulting in tissue damage) or increased reabsorption from the gut into circulation (Zeng et al , 2023). Histological examination of liver and damage markers showed no evidence of cholestasis, as morphology of bile canaliculi was normal, no signs of necrosis were present and serum alanine transaminase/aspartate aminotransferase (ALT/AST) were not changed (Figs 2C–E and EV2B).…”
Section: Resultsmentioning
confidence: 99%
“…Bile acids are physiological detergents whose levels are controlled by a balance of enzymes involved in biosynthesis and detoxification, where regulation is responsive to both feedback and feed‐forward mechanisms (Zeng et al , 2023). As MAPL −/− mice showed elevated hepatic bile acid production at fed state, but no liver damage or increased bile acid elimination, we explored in detail the multi‐layered regulation of the pathway within the liver.…”
Section: Resultsmentioning
confidence: 99%
“… 18 , 19 MBSCs likely act as ligands for host bile salt receptors, including farnesoid X receptor (FXR) and pregnane X receptor, and accordingly have the potential to modulate processes controlled by these nuclear receptors. 18 , 20 A recent study demonstrated that several MBSCs inhibit the germination of Clostridium difficile spores in vitro, pointing toward the a role of MBSCs in bacterial communication. 14 Analysis of public mass spectrometry datasets revealed an association between fecal MBSC abundance ( viz.…”
Section: Introductionmentioning
confidence: 99%
“…CLD is associated with the accumulation of bile acids (BAs) in the liver, resulting in liver inflammation, hepatocyte damage, and liver fibrosis and cirrhosis, for which treatment options are limited ( Goodman, 2007 ; Gines et al, 2021 ). Persistent cholestasis may lead to chronic inflammatory responses within the liver and damage bile duct cells and hepatocytes ( Cai et al, 2017 ; Zeng et al, 2023 ). Various factors associated with hepatocyte apoptosis and necrosis, including inflammation in the liver and activation of Kupffer cells, trigger the secretion of pro-inflammatory cytokines ( Kisseleva and Brenner, 2021 ).…”
Section: Introductionmentioning
confidence: 99%